Regulatory roles of ferroptosis-related non-coding RNAs and their research progress in urological malignancies - Wang, Shijin; Jiang, Bowen; Xie, Deqian; Li, Xiunan; Wu, Guangzhen (Frontiers in Genetics, 2023)
Ferroptosis is a new type of cell death characterized by damage to the intracellular microenvironment, which causes the accumulation of lipid hydroperoxide and reactive oxygen species to cause cytotoxicity and regulated cell death. Non-coding RNAs (ncRNAs) play an important role in gene expression at the epigenetic, transcriptional, and post-transcriptional levels through interactions with different DNAs, RNAs, or proteins. Increasing evidence has shown that ferroptosis-related ncRNAs are closely related to the occurrence and progression of several diseases, including urological malignancies. Recently, the role of ferroptosis-associated ncRNAs (long non-coding RNAs, micro RNAs, and circular RNAs) in the occurrence, drug resistance, and prognosis of urological malignancies has attracted widespread attention. However, this has not yet been addressed systematically. In this review, we discuss this issue as much as possible to expand the knowledge and understanding of urological malignancies to provide new ideas for exploring the diagnosis and treatment of urological malignancies in the future. Furthermore, we propose some challenges in the clinical application of ferroptosis-associated ncRNAs.